Analysis of Organizational Communication Ethics on Employee Performance at PT.BNI Medan Region Retail and Payment Solution Unit - Astrina; Humaizi; Hatta Ridho (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the ethics of organizational communication on employee performance in the acquisition of Quick Response Code Indonesia (QRIS) at PT BNI Medan Medan, Retail and Payment Solutions Unit (SRW). Researchers used organizational communication theory and descriptive qualitative research methods. The informants were 8 (eight) employees of PT BNI Medan Region. Organizational communication that occurs involves communicators, messages, channels, communicants and effects. Intrapersonal and interpersonal conflicts are most often encountered. The obstacles encountered in the SRW unit are VUCA (Volatility, Uncertainty, Complexity, Ambiguity) Era. The organizational communication model formed in the SRW unit of PT BNI Medan Region is vertical and diagonal. The result of this research is that organizational communication ethics in SRW unit runs well in the form of AKHLAK behavior implementation. Communication between employees is an interaction that is the main key in producing quality organizational performance. Organizational performance is determined by the performance of employees either from themselves (internal factors) or derived from the external environment of the organization, as well as the company's strategic efforts. In overcoming obstacles, SRW employees are quite solid and try to minimize conflict. BNI management also actively provides self-development tools for all employees, and reminds employees to behave in accordance with the AKHLAK Core Values.